Questioning the Canon: Feminine English Romanticism (Journal of Bhuwanishankar, 2024)
Addressing the need for the historical phenomenon called Romanticism merits its gendered study or the female-authored Romantic literature. Although the cursory and introductory configurations of the terra incognita might risk the lopsided position, the inclinations to reconfigurations and the question of terra incognita itself are assumed the valuable efforts. This research paper questions the traditional English Romanticism that is all about the Big six male poets Wordsworth, Coleridge, Blake, Shelly, Keats and Byron. This paper, thus, employs the comparative analysis method embedded in the textual analysis method. The analytical framework includes: the inclusion of critical statements and the incorporation of conventional themes. To that end, two representative women poets of Romanticism: Felicia Dorothea Hemans and Mary Robinson and their four poems have been chosen for consideration. Hemans’ “Casabianca” and “I Dream of All Things Free”; Robinson’s “Ode to Beauty” and “Elegy on the Death of Lady Middleton”. The analysis has established the need for alternative Romanticism: Feminine Romanticism is an effort to question the hegemonic masculine Romanticism. Female writers also have been adequately capable of pursuing the continuities and innovations in regard to the Romantic studies.